School + Family Community Learning Model of PE Course under COVID-19 Epidemic Situation - Lu, Senzhao (International Journal of Emerging Technologies in Learning (iJET), 2020)
Influenced by COVID-19 epidemic, students cannot learn PE course offline, and online live streaming becomes a main method under the epidemic situation. How to guarantee students’ learning quality at home and communication among students, parents and teachers is a matter of concern. Besides, traditional PE teaching model also has many defects, and students’ dependence on the teacher is strong. On this basis, the school + family community learning model was constructed in this study based on big data technique and online teaching under the COVID-19 epidemic situation. This model takes the collaboration among students, parents and teachers as the core and key, aims to improve teachers’ online teaching effect and students’ online learning quality, including four stages: connection stage, adaptation stage, proficiency stage and integration stage. In addition, this model was applied in PE teaching in combination of cooperative learning. Meanwhile, the main first-level evaluation indexes of the model were developed, including teaching and resource platform, infrastructure, environment and layout, IoT application, intelligent recording and playing, training scheme, intelligent control and perception. The teaching effect was verified by the questionnaire method, and the result demonstrates that the teaching model improves both teachers’ online teaching capability and students’ online learning quality.